Characterizing Almost Quasi-\(Γ\)-ideals and Fuzzy Almost Quasi-\(Γ\)-ideals of \(Γ\)-semigroups - Simuen, Anusorn; Wattanatripop, Khwancheewa; Chinram, Ronnason (Communications in Mathematics and Applications, 2020)
In this paper, we dene the concepts of almost quasi-\(Γ\)-ideals and almost quasi-\(Γ\)-ideals of a \(Γ\)-semigroup. Moreover, we give some relationship between almost quasi-\(Γ\)-ideals and fuzzy almost quasi-\(Γ\)-ideals of \(Γ\)-semigroups.